Oral versus intravenous iron therapy among pregnant women with iron deficiency anaemia: a comparative study - Tonge, Ganesh; Dasila, Priyank Singh; Pote, Tejaswini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anaemia during pregnancy is considered to be a serious health concern. Whilst oral supplementation is most prevalent, it is also possible to provide iron parentally to replace the deficit. Methods: An observational study was conducted in the department of obstetrics and gynaecology of a tertiary care hospital, in Maharashtra. Total 110 women with iron deficiency anaemia were randomly divided into two groups using computer generated random numbers. Group A received oral iron therapy and group B received intravenous sucrose therapy. The haemoglobin and serum ferritin were assessed before and after treatment. Results: In the oral iron therapy group the age ranged between 19.3 to 27.1 years and in intravenous iron therapy group from 19.2 and 26.5 years. Baseline (0 day) haemoglobin in oral iron therapy group was 8.21±1.12 gm/dl and 8.36±1.14 gm/dl in intravenous iron group. The mean difference of 3.38 gm/dl was seen in the intravenous therapy group at 8th weeks against the mean difference of 1.63 gm/dl in oral iron therapy group. The mean difference of serum ferritin 18.92 µg/l was found in the oral iron therapy at the 8th week while the mean difference of 63.79 µg/l was seen in the intravenous therapy group. Conclusions: The intravenous sucrose therapy is found to be safe and effective alternative treatment for iron deficiency anaemia in pregnancy though the cost of treatment is significantly higher than the oral therapy.